34.0k views
3 votes
Find the differential coefficient of

e^(2x)(1+Lnx)

2 Answers

4 votes

Answer:

Product Rule for Differentiation


\textsf{If }y=uv


(dy)/(dx)=u(dv)/(dx)+v(du)/(dx)

Given equation:


y=e^(2x)(1+\ln x)

Define the variables:


\textsf{Let }u=e^(2x) \implies (du)/(dx)=2e^(2x)


\textsf{Let }v=1+\ln x \implies (dv)/(dx)=(1)/(x)

Therefore:


\begin{aligned}(dy)/(dx) & =u(dv)/(dx)+v(du)/(dx)\\\\\implies (dy)/(dx) & =e^(2x) \cdot (1)/(x)+(1+\ln x) \cdot 2e^(2x)\\\\& = (e^(2x))/(x)+2e^(2x)(1+\ln x)\\\\ & = (e^(2x))/(x)+2e^(2x)+2e^(2x) \ln x\\\\& = e^(2x)\left((1)/(x)+2+2 \ln x \right)\end{aligned}

User Budda
by
5.0k points
6 votes

Answer:


\rm \displaystyle y' = 2 {e}^(2x) + (1)/(x) {e}^(2x) + 2 \ln(x) {e}^(2x)

Explanation:

we would like to figure out the differential coefficient of
e^(2x)(1+\ln(x))

remember that,

the differential coefficient of a function y is what is now called its derivative y', therefore let,


\displaystyle y = {e}^(2x) \cdot (1 + \ln(x) )

to do so distribute:


\displaystyle y = {e}^(2x) + \ln(x) \cdot {e}^(2x)

take derivative in both sides which yields:


\displaystyle y' = (d)/(dx) ( {e}^(2x) + \ln(x) \cdot {e}^(2x) )

by sum derivation rule we acquire:


\rm \displaystyle y' = (d)/(dx) {e}^(2x) + (d)/(dx) \ln(x) \cdot {e}^(2x)

Part-A: differentiating $e^{2x}$


\displaystyle (d)/(dx) {e}^(2x)

the rule of composite function derivation is given by:


\rm\displaystyle (d)/(dx) f(g(x)) = (d)/(dg) f(g(x)) * (d)/(dx) g(x)

so let g(x) [2x] be u and transform it:


\displaystyle (d)/(du) {e}^(u) \cdot (d)/(dx) 2x

differentiate:


\displaystyle {e}^(u) \cdot 2

substitute back:


\displaystyle \boxed{2{e}^(2x) }

Part-B: differentiating ln(x)e^2x

Product rule of differentiating is given by:


\displaystyle (d)/(dx) f(x) \cdot g(x) = f'(x)g(x) + f(x)g'(x)

let


  • f(x) \implies \ln(x)

  • g(x) \implies {e}^(2x)

substitute


\rm\displaystyle (d)/(dx) \ln(x) \cdot {e}^(2x) = (d)/(dx)( \ln(x) ) {e}^(2x) + \ln(x) (d)/(dx) {e}^(2x)

differentiate:


\rm\displaystyle (d)/(dx) \ln(x) \cdot {e}^(2x) = \boxed{(1)/(x) {e}^(2x) + 2\ln(x) {e}^(2x) }

Final part:

substitute what we got:


\rm \displaystyle y' = \boxed{2 {e}^(2x) + (1)/(x) {e}^(2x) + 2 \ln(x) {e}^(2x) }

and we're done!

User Lvarayut
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.